Determinants of Health Behavior in Public Health Promotion: A Critical Review - Nur Ekawati; Pusfitasari; Andi Asrina; Yusriani; Fairus Prihatin Idris (STIKes Budi Luhur Cimahi, 2026)
Health behavior is a major determinant of individual and population health and is shaped by multiple interacting factors across different levels of influence. This study aimed to critically analyze the determinants of health behavior and their implications for public health promotion. A critical review was conducted using a transparent study selection process guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020). Electronic searches were performed in PubMed, Scopus, ScienceDirect, and Google Scholar, resulting in 39 studies published between 2021 and 2026 that met the predefined eligibility criteria. Methodological quality was critically appraised using design-specific assessment tools, and the evidence was examined through analytical and interpretive synthesis. Six major categories of health behavior determinants were identified: individual, social, environmental, cultural and religious, technological, and policy determinants. Individual determinants, particularly health literacy, self-efficacy, knowledge, motivation, and health beliefs, were the most frequently examined. However, the synthesis demonstrated that these determinants did not operate independently but interacted with social relationships, environmental opportunities, cultural contexts, technological conditions, and policy environments. The review identified several theoretical, methodological, and empirical gaps, including the predominance of individual-level perspectives and limited attention to interactions among contextual and structural determinants. These findings highlight the need for multilevel, context-sensitive, and theoretically integrated health promotion strategies that simultaneously address individual capabilities and the broader social, environmental, cultural and religious, technological, and policy conditions shaping health behavior.